2023
DOI: 10.1021/acsami.3c00618
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning-Aided Band Gap Engineering of BaZrS3 Chalcogenide Perovskite

Abstract: The non-toxic and stable chalcogenide perovskite BaZrS3 fulfills many key optoelectronic properties for a high-efficiency photovoltaic material. It has been shown to possess a direct band gap with a large absorption coefficient and good carrier mobility values. With a reported band gap of 1.7–1.8 eV, BaZrS3 is a good candidate for tandem solar cell materials; however, its band gap is significantly larger than the optimal value for a high-efficiency single-junction solar cell (∼1.3 eV, Shockley–Queisser limit)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…21 The Troullier-Martins norm-conserving pseudopotentials are adopted to calculate the ground-state Kohn-Sham wave functions and eigenvalues as implemented in the QUANTUM ESPRESSO code. 22 The kinetic energy cutoff of 60 (10) Ry is used for the wave function (dielectric matrix) and the screened Coulomb energy cutoff of 10 Ry and the bare Coulomb energy cutoff of 70 Ry are used to compute the selfenergy. The 8 Â 8 Â 1 k-point mesh is adopted for GW calculations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…21 The Troullier-Martins norm-conserving pseudopotentials are adopted to calculate the ground-state Kohn-Sham wave functions and eigenvalues as implemented in the QUANTUM ESPRESSO code. 22 The kinetic energy cutoff of 60 (10) Ry is used for the wave function (dielectric matrix) and the screened Coulomb energy cutoff of 10 Ry and the bare Coulomb energy cutoff of 70 Ry are used to compute the selfenergy. The 8 Â 8 Â 1 k-point mesh is adopted for GW calculations.…”
Section: Methodsmentioning
confidence: 99%
“…9 Recent developments include the use of first-principles calculations and machine learning algorithms to tune the bandgap of BaZrS 3 chalcogenide perovskite for photovoltaic applications, with Ca doping at the Ba site showing promise as the optimal dopant. 10 Experimental efforts have led to the preparation of distorted perovskites such as BaZrS 3 , 11 SrZrS 3 , 11 BaHfS 3 , 12 SrHfS 3 , 12 and BaZr(S 1Àx Se x ) 3 11 through solid-state reactions, showcasing remarkable band-edge absorption. Additionally, BaZrS 3 , CaZrS 3 , SrZrS 3 , and SrTiS 3 perovskites have been synthesized through high-temperature sulfurization of their oxide counterparts, 13 with the ability to tune their band gaps through an anion alloying approach.…”
Section: Introductionmentioning
confidence: 99%
“…Bandgap engineering using machine learning and first principle calculations is adopted by Sharma et al to reduce the bandgap of BaZrS 3 for creating the best composition of BaZrS 3 . Their results indicate that partial doping of Ca at the Ba site and Ti at the Zr site to make the composition Ba 1-x Ca x ZrS 3 and Ba(Zr 1-x Ti x )S 3 respectively [71] produces better optoelectronic materials. A series of distorted perovskites ASnX 3 (X=S/Se) compounds are screened by Ju et al [21] They have shown from the first principle calculation that SrSnS 3 and SrSnSe 3 compounds have optimal band gaps (0 .9-1.6 eV) and absorption coefficients similar to MaPbI 3 .…”
Section: Computer Aided Design Of Chalcogenide Perovskitementioning
confidence: 99%
“…to reduce the bandgap of BaZrS 3 for creating the best composition of BaZrS 3 . Their results indicate that partial doping of Ca at the Ba site and Ti at the Zr site to make the composition Ba 1‐x Ca x ZrS 3 and Ba(Zr 1‐x Ti x )S 3 respectively [71] produces better optoelectronic materials. A series of distorted perovskites ASnX 3 (X=S/Se) compounds are screened by Ju et al [21] .…”
Section: Computer Aided Design Of Chalcogenide Perovskitementioning
confidence: 99%
“…They grabbed the limelight in 2015 when Sun et al theoretically screened 18 ABX 3 (A = Ba, Sr, Ca; B = Ti, Zr, Hf; X = S, Se) compounds to be promising for optoelectronic applications. 33 Among them, BaZrS 3 is considered to be ideal from the standpoint of the direct band gap of 1.7 eV, 34 high absorption coefficient >10 5 cm −1 at photon energy larger than 1.97 eV (<700 nm), 35 elevated carrier mobility of 30 cm 2 /(V s) with p-type conductivity, 36 and exceptional stability toward moisture, light, and temperature. 37 Prior research indicates that the performance of BaZrS 3 can be improved further by alloying with both titanium (Ti) and selenium (Se).…”
Section: Introductionmentioning
confidence: 99%